2015
DOI: 10.1063/1.4931766
|View full text |Cite
|
Sign up to set email alerts
|

Overview spectra and axial distribution of spectral line intensities in a high-current vacuum arc with CuCr electrodes

Abstract: Spectroscopic investigations of free-burning vacuum arcs in diffuse mode with CuCr electrodes are presented. The experimental conditions of the investigated arc correspond to the typical system for vacuum circuit breakers. Spectra of six species Cu I, Cu II, Cu III, Cr I, Cr II, and Cr III have been analyzed in the wavelength range 350-810 nm. The axial intensity distributions were found to be strongly dependent on the ionization stage of radiating species. Emission distributions of Cr II and Cu II can be dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However, a bright glowing region near the anode is also seen in figure 5. Considering the results in other studies [9], glowing near the anode can be explained by the presence of a zone with high-density metallic atoms.…”
Section: The Vacuum Arc In Diffuse Modementioning
confidence: 50%
See 1 more Smart Citation
“…However, a bright glowing region near the anode is also seen in figure 5. Considering the results in other studies [9], glowing near the anode can be explained by the presence of a zone with high-density metallic atoms.…”
Section: The Vacuum Arc In Diffuse Modementioning
confidence: 50%
“…To obtain a deeper understanding of the physical process in vacuum arcs and dielectric recovery process after arc extinction, vacuum arc studies and metallic vapor density measurements are useful. Lisnyak [9] investigated the axial distribution of spectral line intensities of vacuum arcs operating in the diffuse mode using optical emission spectroscopy (OES). His results show that the intensity maxima of excited atoms occur near the electrodes, which suggests a non-uniform distribution of metallic vapor density during the arcing period.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the arc shape is mainly based on the movement and distribution of spots and arc column under different conditions [2][3][4][5]. Some scholars use the emission spectrum, absorption spectrum, laser-induced fluorescence and other methods to realize the observation of the vacuum arc and acquire the 1D [6][7][8][9][10][11][12][13][14][15] or 2D distribution of the spectral line intensity and the particle density. Compared with the emission spectrum, the diagnostic system composition of absorption spectrum and laser-induced fluorescence method are more complex, through the external light source radiation to achieve the excitation and transition of particles in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the main spectral lines of the vacuum arc at low current are atomic and univalent ionic lines. Lnyak et al [7] studied the axial distribution of the intensity of spectral lines of the vacuum arc in the diffused state and the high-current contraction state, and found that the maximum intensity of the atomic emission lines appeared near the electrode, the spatial distribution of metal vapor was uneven, and there was a unique emission peak of bivalent copper ions near the anode. At the same time, the distribution of spectral lines of atoms, univalent and bivalent copper ions with different electrode materials are studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various power system requirements, it is crucial that currents be interrupted reliably, especially short-circuit currents, and this reliability is closely related to dielectric recovery after vacuum arc extinction. It is believed that metal vapor combined with other factors like residual plasma and liquid droplets dominates the dielectric recovery process after the current reaches zero [3][4][5][6]. However, it could be observed that long-delayed breakdown occurs several or hundreds of milliseconds after current extinction, and this phenomenon cannot be attributed to the factors mentioned above [7,8].…”
Section: Introductionmentioning
confidence: 99%